Finance of the Municipal Sector in Comparison with Public Finance of the European Union Countries - Agnieszka Alińska (Contemporary Economics)
The general financial situation of municipal government in the European Union countries seems to be very good. The dynamics of tax income value growth achieved by local and regional authorities considerably exceed the figures characterizing the all public sector. Moreover, municipal authorities at the local and regional level are a leading public investor in many EU countries, they finance 69,3% of all public investments in average in all EU. Besides the value of their budget deficits, at the level of 0,2% GDP, and also their share in values of the national debt at the level of 5,8% GDP the European Union can be qualified as safe having no negative impact on getting positive economic effects in many countries of the European Union.